PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V B SD NEGERI 125 PEKANBARU - Dian Oktavia; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low learning outcomes of science of student grade V B SD Negeri 125 Pekanbaru. From 23 students, there are at least 8 students (34,78%) who achieved the Minimum Completess Criteria (scores 75), and 15 students (65,22%) are being below of the Minimum Completess Criteria with class average is 64,56. The low of student studies outcomes are caused by more active teachers rather than students in ongoing learning. So they don’t have the opportunity to develop their knowledge. The aim of this research is to improve the outcomes of science studies of student grade V B SD Negeri 125 Pekanbaru with the implementation of the cooperative learning model of the take and give type. This research uses Classroom Action Research which is done in 2 cycles methods with qualitative data analysis techniques. This research present studies result obtained from daily test scores before action with average 64,56 increase to 72,82 in first cycle, and increase again to 83,48 in second cycle. The activvity of teacher in the first cycle of the first meeting is 64% with enough criteria, the second meeting is 77% with good criteria. In second cycle of the first meeting is 86% with very good criteria, the second meeting is 90% with very good criteria. The activity of student in first cycle of the first meeting is 63% with enough criteria, the second meeting is 72% with enough criteria. For awhile in second cycle of the first meeting is 84% with good criteria, and the second meeting is 89% with very good criteria. Based of the outcomes of the studies it can be proven that the implementation of the cooperative learning model of the take and give type can improve the science studies outcomes of student grade V B SD Negeri 125 Pekanbaru.Key Words : Take and Give, Science Studies Learning